Understanding students' and clinicians' experiences of informal interprofessional workplace learning: an Australian qualitative study. Issue 4 (17th April 2018) - Rees, Charlotte E; Crampton, Paul; Kent, Fiona; Brown, Ted; Hood, Kerry; Leech, Michelle; Newton, Jennifer; Storr, Michael; Williams, Brett
Abstract : Objectives: While postgraduate studies have begun to shed light on informal interprofessional workplace learning, studies with preregistration learners have typically focused on formal and structured work-based learning. The current study investigated preregistration students' informal interprofessional workplace learning by exploring students' and clinicians' experiences of interprofessional student-clinician (IPSC) interactions. Design: A qualitative interview study using narrative techniques was conducted. Setting: Student placements across multiple clinical sites in Victoria, Australia. Participants: Through maximum variation sampling, 61 participants (38 students and 23 clinicians) were recruited from six professions (medicine, midwifery, nursing, occupational therapy, paramedicine and physiotherapy). Methods: We conducted 12 group and 10 individual semistructured interviews. Themes were identified through framework analysis, and the similarities and differences in subthemes by participant group were interrogated. Results: Six themes relating to four research questions were identified: (1) conceptualisations of IPSC interactions; (2) context for interaction experiences; (3) the nature of interaction experiences; (4) factors contributing to positive or negative interactions; (5) positive or negative consequences of interactions and (6) suggested improvements for IPSC interactions. Seven noteworthy differences in subthemes between students and clinicians and across the professions were identified. Conclusions: Despite the results largely supporting previous postgraduate research, the findings illustrate greater breadth and depth of understandings, experiences and suggestions for preregistration education. Educators and students are encouraged to seek opportunities for informal interprofessional learning afforded by the workplace.